Problem Paradigmatik Pendekatan Saintifik dalam Pembelajaran Agama Islam - Hafisyah, Siti (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2021)
The curriculum is the lifeblood of education, because all things related to education come from the curriculum, material content, learning strategies, and methods used. The government very concerned with education because the good character and behaviour of the nation next generation depends on the quality of the education itself, the quality of education is good if the curriculum used is also of quality, the government’s efforts to improve education are proven by the improvement of the education unit level curriculum into a national curriculum, namely the two thousand and thirteen curriculum. In this curriculum, the method used is using the scientific method with the learning steps of observing, asking, trying, associating and communicating. The scientific method itself seems to be more identical with science and science subjects, but it turns out that the scientific method can be used in Islamic education subjects, according to the journals that the researchers read, many schools have started Islamic education lessons used the scientific method, some can carry out learning well, but not a few teachers who have difficulty in applying this scientific method, these obstacles can come from the curriculum itself, from teachers, even come from students who are objects. The most felt obstacles in the application of the scientific method of learning Islamic education include the uneven creativity of the teacher to be able to make learning accepted by students, the psychology of the students being another obstacle, the lack of facilities and available media so that they cannot provide education optimally. So it takes the cooperation of all elements to be able to create scientific-based Islamic education.